THE EFFECT OF FOOD POISONING VICTIM EVACUATION TRAINING ON THE SKILLS OF TEACHERS AT SLB NEGERI 1 BANTUL - M Farhan Khoirullah; Gatot Suparmanto; Heri Puspito (Journal of Indonesian Anesthesiology Nursing, 2026)
Background: Food poisoning remains a common health problem in schools and may lead to emergency situations. In Bantul, a previous study reported that 53.4% of students experienced food poisoning symptoms due to bacterial contamination. As first responders, teachers need adequate evacuation skills to provide prompt and appropriate initial management. However, most teachers have never received food poisoning victim evacuation training. Methods: This quantitative study used a pre-experimental one-group pretest-posttest design. The sample consisted of 51 teachers selected through simple random sampling. Data were collected using an observation checklist before and after the training. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: Before the training, most respondents were categorized as less skilled (47 teachers; 92.2%). After the training, the majority were categorized as skilled (31 teachers; 60.8%). The Wilcoxon Signed-Rank Test showed that food poisoning victim evacuation training significantly affected teachers’ skills at SLB Negeri 1 Bantul (p=0.000; p<0.05). Conclusion: Food poisoning victim evacuation training significantly improved teachers’ skills at SLB Negeri 1 Bantul